INCORPORATING ETHNOMATHEMATICS AND REALISTIC MATHEMATICS EDUCATION ON DEVELOPING MATHEMATICS CONNECTION USING THE MENARA KUDUS - Sari, Sellanidia Antika; As-salamah, Siti Fatimah; Maharani, Rizqona; Nisa', Silvia Durrotun (Ethnomathematics Journal, 2024)
This research was motivated by students' low mathematical connections and lack of knowledge about the local culture around where they live. This research aims to develop a student digital worksheet using the concepts of ethnomathematics and Realistic Mathematics Education following  the ADDIE procedure. A number of 30 students of year five in a primary school in Kudus District, Province of Central Java, Indonesia, involved in the study. The learning material used the local cultural object namely Menara Kudus. This bulding is part of muslim gathering venue and known its adaptation to the Hinduism as it was built during the era. A digital worksheet is defined as a set learning activity that can be accessed using electronic gadgets, like computer or smartphone. Validation of the development resutls included experts and students to collect data on the feasibility assessment of the digital worksheet which consists of assessments by material experts and media experts. In addition, the use of web based interactive worksheets at Menara Kudus based on Ethno–RME shows a significant increase in students' mathematical connections. This means that the Ethno–RME based Digital worksheet at the Menara Kudus was declared feasible and can be used in mathematics learning.